Thermal Desorption of 2,4,6-Trichloroanisole from Cork - Susana Monteiro; Nenad Bundaleski; Paulo Lopes; Miguel Cabral; Orlando M.N.D. Teodoro (Foods, 2023)
While extensive efforts have been made over the past two decades to understand how cork becomes contaminated by 2,4,6-trichloroanisole (TCA), the nature of its bond to cork remains unclear. A deeper understanding of this interaction is crucial in designing processes to effectively remove TCA from cork stoppers. This study presents an investigation into the thermal desorption of TCA from cork under vacuum conditions. To facilitate detection by a quadrupole mass spectrometer, samples were artificially contaminated with sufficient TCA. A calibration system was developed to determine the absolute rate of TCA released from the cork. Desorption spectra revealed two peaks at 80 °C and 170 °C. Despite the known variability of cork, repeated measurements demonstrated reasonable repeatability. The low-temperature peak decreased with time and after preheating the sample to 50 °C. It is proposed that the high-temperature peak corresponds to TCA bonded to the cork material. Experiments with naturally contaminated cork stoppers revealed a significant reduction in the amount of releasable TCA following a vacuum-heating process. This study provides an insightful discussion on the adsorption of TCA on cork and proposes an estimate for the adsorption energy. Furthermore, it discloses a process capable of removing TCA from natural cork stoppers.